Prototype Mini Crane Pemindah Barang Berbasis Sistem Otomasi - Aldi Alamsyah; Hendi Purnata; Muhammad Yusuf (Jurnal Jaringan Telekomunikasi, 2021)
Crane is a tool used to make it easier to move and lift an item. This research aims to create a mini crane system for optimizing the movement of goods based on industrial automation that utilizes PLC (programmable logic controller) as the controller and Pneumatik s as the actuator. This system uses a Mitsubishi PLC as the main controller. PLC works based on the input obtained from the selector switch to select a manual or automatic work system. There is a push button as a start and stop button, a limit switch as a limiter for the movement of the X and Y axes of the Rodless Cylinder to move items, proximity sensors to detect the presence of items to be moved and those that have been moved. In the results of this study, the sensor used to detect the type of workpiece material uses an inductive proximity sensor. In one crane process takes a maximum of 15.37 seconds. The maximum weight that a vacuum can suck at a pressure of 3 bar is 650g, at a pressure of 4 bar it is 950g, and at a pressure of 6 bar it is 1059g.